Communication controller design for an electric vehicle charging station - Loureiro, José Pedro Freitas (2024)
The recent surge in electric mobility for road vehicles is a direct response to the substantial pollution generated throughout the lifespan of combustion vehicles. Consequently, to combat this issue and contribute to a greener and more sustainable planet, the establishment of a robust network of Electric Vehicle Supply Equipment (EVSE) is imperative. Among the various available charging modes and their respective protocols, the Combined Charging System (CCS) protocol stands out in Europe as the most used, as it is very robust and facilitates both Alternating Current (AC) and Direct Current (DC) fast charging. For DC charging under this protocol, an Electric Vehicle (EV) interface communication controller on the charger side is essential for enabling communication between the EV and the Supply Equipment. This thesis outlines the development of a Supply Equipment Communication Controller (SECC) circuit that complies with the specified standards of the CCS protocol. The primary function of the controller is to establish a bidirectional com munication interface between the charger central unit and the EV. This is achieved through Power-line Communication (PLC) and a low-level Pulse-width Modulation (PWM) signal transmitted in the same line, for communication with the vehicle, while communication with the charger processing controllers is accomplished via Controller Area Network (CAN). After an extensive analysis and comparison, the most crucial System on a Chip (SoC) selected for the project are introduced. These include the Microcontroller Unit responsible for the controller processing and the intricate PLC chip, which manages the communication interface with the EV. Subsequently, the remaining designed and implemented circuits are presented, encompassing voltage supply circuits, communication interface circuits, and auxiliary circuits required for the communication with the electric vehicle. Finally, circuit simulations were conducted on specific parts of the circuit to ensure overall compliance with the system requirements.